Molecular and morphological factors contributing to the resolution of the taxonomy of Octopus vulgaris Type III - Fee, Gareth (Department of Biological Sciences, 2025)
Cryptic species are common in the marine environment, particularly among invertebrates. The genus Octopus Cuiver, 1797 is considered a ‘catch all' genus due to the lack of morphological traits available to distinguish closely-related species. In recent years, the Octopus vulgaris species complex has received much attention with many cryptic species ‘Types' being identified, most of which have now been re- or newly described as separate species. The last remaining Type currently known within this complex which requires taxonomic resolution is the Southern African lineage, Octopus vulgaris Type III. This taxon was not included in a recent global morphological assessment of the complex and few specimens were included in phylogenetic studies. Mitochondrial barcodes failed to distinguish O. vulgaris Type III from O. vulgaris sensu stricto (ss), but nuclear genes did. This dissertation aims to resolve the taxonomy of O. vulgaris Type III using both genetic and morphological lines of evidence. Chapter 1 gives a broad background to the cryptic species problem within cephalopods and discusses the significance of resolving the taxonomy of O. vulgaris Type III. Chapters 2 and 3 sequence and annotate the first complete mitochondrial genomes (mitogenomes) of O. vulgaris ss and O. vulgaris Type III respectively. Chapter 2 also includes a phylogenomic assessment and found O. vulgaris Type III to be a sister taxon to O. vulgaris ss, separated with high statistical support. Chapter 4 presents a detailed morphological assessment of O. vulgaris Type III, which successfully delimit it from all other species within the species complex. Finally, Chapter 5 summarises these findings. These results have significant implications, considering the growing octopus fishery in South Africa, as management should consider the population as an isolated species, distinct from O. vulgaris ss, which is found in the Mediterranean and Northeast Atlantic.